Analysis the Influence of Topic Types and Posting Days on User Engagement: A Case Study of the XYZ Instagram Account - Aaron Arthasastra Jeheskiel Rawung; Timothy Alesandro Mangare; Jimmy Herawan Moedjahedy (Apollo: Journal of Tourism and Business, 2026)
This study examines how content type and posting day affect user engagement on the XYZ Instagram account. As technology advances, traditional media outlets increasingly rely on social platforms to reach broader audiences. Understanding engagement factors is crucial for effective digital communication strategies. While digital transformation has pushed traditional media toward social platforms, identifying consistent content-market fit remains a challenge. Using a quantitative approach, this research analyzed 190 posts categorized by topic informative, entertainment, political and posting day Monday to Friday using Kruskal-Wallis tests. The research analyzed posts from the XYZ account to identify patterns and significant relationships. Results reveal content type significantly affects only view counts, while posting day impacts only likes. The combination of both factors shows more substantial influence, affecting likes, views, and average watch time. However, since most engagement indicators showed no significant differences across conditions, content type and posting day don't consistently predict user interaction levels. The findings reveal that while individual factors, content type and posting day show limited significance on their own, their interaction effect is statistically significant for likes, views, and average watch time. This suggests that engagement is not driven by content or timing in isolation, but by the strategic synchronization of what is posted and when. While certain combinations of content and timing may boost specific engagement metrics, the research suggests other factors may play more decisive roles in determining overall social media performance and audience connection.